Minimal point volumetric outlining and editing for radiotherapy treatment planning. Issue 3 (1st September 2017) - Bridge, Pete; Fielding, Andrew; Rowntree, Pamela; Pullar, Andrew
Abstract: Purpose: A novel radiotherapy outlining application uses a small number of user-assigned points across orthogonal planes to generate a mesh which is then edited across multiple slices using innovative three-dimensional (3D) sculpting tools. This paper presents the results of a bladder outlining study that compared times and volumes for the new tool with those of a conventional manual outlining tool. Materials and methods: All students undertaking their first University radiotherapy planning module were invited to participate. Following training, they performed a timed outlining of the same male bladder dataset and provided feedback on their preferred method. Results: Comparison of times from the resulting ten datasets demonstrated that the 3D segmentation tool was significantly faster than conventional software with a mean time of 11·9 minutes compared with 19·2 minutes ( p =0·03). The users expressed a preference for the new tool (eight users) over the conventional outlining software (two users). Conclusions: A minimal point 3D volumetric manual outlining tool utilising orthogonal computed tomography planes demonstrated significant time saving for bladder segmentation compared with axial-based outlining within a group of novice outliners. Future work aims to establish the role of the 3D multi-slice sculpting tools in editing of auto-segmentation derived contour sets.